(untitled) (The Pretoria Student Law Review, 2021)
The discussion to follow aspires to take a closer look at the birth of the Roman debt collecting system and trace the development for approximately a thousand years, with the aim of clarifying the present state of the law by showing its evolution over time. However, before venturing into the depths of ancient Rome, a thorough understanding of the application of Roman law in South Africa is crucial.